The Effect of Collegial Supervision and School Organizational Culture on Teacher Performance - Hayati, Elis; Sururi, Sururi; Rahyasih, Yayah (Jurnal Pendidikan (Teori dan Praktik), 2026)
This study investigates the effects of collegial supervision and school organizational culture on elementary school teacher performance in Indonesia, grounded in the growing recognition of collaborative professional development. Using a quantitative survey of 300 teachers from 51 public schools in Purwakarta Regency, data were analyzed through Structural Equation Modeling. The measurement instruments showed strong validity and reliability. The results indicate that collegial supervision is implemented at a good level and has a significant effect on teacher performance, while school organizational culture also contributes significantly, though to a lesser extent. Together, both variables explain 8.7 percent of the variance in teacher performance and demonstrate predictive relevance. The study concludes that collegial supervision plays a meaningful role in enhancing teacher performance when supported by a positive and well-established organizational culture, offering important implications for strengthening teacher development practices in Indonesian elementary schools.